2021
DOI: 10.48550/arxiv.2109.07382
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Toward Modern Fortran Tooling and a Thriving Developer Community

Abstract: Fortran is the oldest high-level programming language that remains in use today and is one of the dominant languages used for compute-intensive scientific and engineering applications. However, Fortran has not kept up with the modern software development practices and tooling in the internet era. As a consequence, the Fortran developer experience has diminished. Specifically, lack of a rich general-purpose library ecosystem, modern tools for building and packaging Fortran libraries and applications, and online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…acknowledge Research Computing at Arizona State University for providing HPC and storage resources that have contributed to the research results reported within this paper. R.C also acknowledge valuable help received from Fortran-lang community [36,37]. In particular, R.C.…”
Section: Declarationsmentioning
confidence: 96%
See 3 more Smart Citations
“…acknowledge Research Computing at Arizona State University for providing HPC and storage resources that have contributed to the research results reported within this paper. R.C also acknowledge valuable help received from Fortran-lang community [36,37]. In particular, R.C.…”
Section: Declarationsmentioning
confidence: 96%
“…Besides, unlike some other MCPEM algorithms, in RPEM the corresponding estimators Eq. (36) and Eq. ( 40) are unbiased estimators.…”
Section: Recap Of Rpemmentioning
confidence: 99%
See 2 more Smart Citations
“…To address these issues, a new open source Fortran community called Fortran-lang was formed in December 2019 [8]. Its initial conception came about in the J3 Fortran Proposals repository on GitHub, described in a later section, where it became clear that there was a need for modern tooling and an improved web presence for the Fortran community.…”
Section: A New Community For Fortran Usersmentioning
confidence: 99%